PENGARUH MAHASISWA MEMILIH JURUSAN AKUNTANSI DI UNIVERSITAS SWASTA DAN UNIVERSITAS NEGERI DI KOTA MEDAN - Vina Arnita (Jurnal Akuntansi Bisnis dan Publik, 2019)
This study explores the influential factors that affect accounting students’ selection of accounting major course of study at the fifth semester and seventh semester in private and public universities in Medan . The present research examined the differences in the impact that various influential factors had on the decision to major in accounting among students studying at private and public universities in Medan. The sample wascollected from a survey of undergraduate and graduate students studying at two large private and public universities in Medan. A total of 100 students participated in this study. The results showed that accounting students possessed higher levels of creativity and were more likely to select accounting major. Conversely, it was found that although public university students possessed relatively highest levels of creativity, they weremore likely to major in accounting when studying in public university. Another finding from this study was that public students perceived the accounting profession as a career with less procedural characteristics so they were more likely to major in accounting compared to private university . This paper contributes to a better understanding of the differences in students’ creativity and procedural images of the accounting profession among private and public students and of how these factors influenced their choice of an accounting major.